Heatwave Advice : Supporting vulnerable people before and during a heatwave : Advice for health and social care professionals.: Supporting vulnerable people before and during a heatwave : Advice for health and social care professionals. ([2018]) - Northern Ireland., Department of Health,
No abstract available